An Analysis on Slang Words in Movie “Agak Laen’’ - Pasaribu, Eka; Sohnata Hutauruk, Bertaria; Silalahi, Dumaris Elseria (Innovative: Journal Of Social Science Research, 2024)
This research examines the slang words used in the utterances of the film "AGAK LAEN." The primary objective of this study is to identify the types and functions of slang words found in the dialogue. The researcher focuses on two main aspects: the variety of slang words used in the film and the functions these slang words serve. The research employs a library research design with a descriptive qualitative method to present the results. Data collection was carried out using documentation techniques. To address the research problem, the researcher applied the theory of slang words put forth by Allan and Burridge (2006). The analysis identified five types of slang words used in the film "AGAK LAEN," which are as follows: fresh and creative with 24 words (48%), flippant with 1 word (2%), imitative with 3 words (6%), acronyms with 6 words (12%), and clipping with 16 words (32%). The functions of the slang words used in the film include: addressing with 9 words (18%), relaxing conversation with 8 words (16%), humiliating with 5 words (10%), creating a casual atmosphere with 2 words (4%), expressing impressions with 17 words (34%), revealing emotions with 3 words (9%), and showing intimacy with 5 words (10%). Slang words are considered non-standard language commonly used in everyday life. They typically serve as a means of communication among teenagers within a specific time frame. The researcher investigates the slang words in "AGAK LAEN," a horror comedy film, chosen for its abundant use of slang throughout the dialogue.